Overview Management Triage at The Emergency Room of The Hospital at Jambi - Imran, Suryadi; Pairi, Agus; Ginting, Marinawati; Erwinsyah, Erwinsyah (West Science Interdisciplinary Studies, 2024)
Triage, which comes from the French word trier, means sorting or sorting patients based on the patient's ABCD, the severity of the injury, the priority scale of the disease emergency, and the patient's life expectancy, so that the time needed to assess and stabilize the patient is not too long. The purpose of triage is not only to provide fast action but also to prevent disability and death of the patient. The research purposes to find out the description of nurses' knowledge regarding triage at the Emergency Room of Hospital Jambi. The design used in this study is descriptive quantitative w. here the variables are examined at the same time which aims to obtain an overview of the level of knowledge of nurses regarding triage in the IGD RS Jambi. samples from all existing populations, namely 50 nurses who were all on duty at the Emergency Room of Hospital. Province Jambi. Conclusion, results this research the level of knowledge of respondents about triage, the researcher can explain that the level of knowledge of respondents about triage is mostly good with a total frequency of 33 people or 66%, while respondents with sufficient knowledge are 17 people or 33%, meaning that most of the 33 respondents have good ability about triage. It can be concluded that the better the level of knowledge of the nurses, the better the understanding of nurses in the implementation of triage in the management emergency room